The effect of brand image and brand awareness on purchasing decisions of pizza hut, Lippo Cikarang mall branch - Zed, Etty Zuliawati; Tri Mulyani Kartini; Andrianto Prasetya Nugroho (SEAN Institute, 2024)
This study aims to analyse the effect of brand image and brand awareness partially and simultaneously on purchasing decisions (y) of Pizza Hut consumers, Lippo Cikarang Branch. The sample in this study were 105 consumers who had purchased Pizza Hut products in Cikarang city at least in the last year. The sampling method used is purposive sampling method. The data analysis method used is multiple linear regression analysis and classical assumption test with the help of the SPSS 16.0 for windows programme. The results showed that simultaneously (F test) purchasing decisions can be influenced by all independent variables and partially showed that only the Brand Awarness variable (X2) had an effect on purchasing decisions (y) while the brand image variable (X1) had no effect. The Brand Awarness variable (X2) has a significance level of 0.000 while the brand image variable has no significant effect on purchasing decisions (y) because it is seen from the sig t level which is 0.090 greater than 0.05. With a coefficient of determination R Square (R2) of 30.9%, which means that the purchasing decision variable (y) can be influenced by the two independent variables while the remaining 69.1% is explained by other factors not explained in this study. Pizza Hut management is advised to continue to update the quality of the company's image and brand image in order to form a positive perception in the eyes of customers, so that it can help maintain the company's image and be able to increase sales.